Tree-based Classifiers for Bilayer Video Segmentation - Yin, Pei; Criminisi, Antonio; Essa, Irfan; Winn, John (Proc. Conf. Computer Vision and Pattern Recognition, 2007)
This paper presents an algorithm for the automatic segmentation of monocular videos into foreground and background layers. Correct segmentations are produced even in the presence of large background motion with nearly stationary foreground. There are three key contributions. The ﬁrst is the introduction of a novel motion representation, “motons”, inspired by research in object recognition. Second, we propose learning the segmentation likelihood from the spatial context of motion. The learning is efﬁciently performed by Random Forests. The third contribution is a general taxonomy of tree-based classiﬁers, which facilitates theoretical and experimental comparisons of several known classiﬁcation algorithms, as well as spawning new ones. Diverse visual cues such as motion, motion context, colour, contrast and spatial priors are fused together by means of a Conditional Random Field (CRF) model. Segmentation is then achieved by binary min-cut. Our algorithm requires no initialization. Experiments on many video-chat type sequences demonstrate the effectiveness of our algorithm in a variety of scenes. The segmentation results are comparable to those obtained by stereo systems.